Learn Ethereum : Build Your Own Decentralized Applications with Ethereum and Smart Contracts. - Wu, Xun (Brian) (Packt Publishing, Limited, 2019)
Chapter 3: Deep Research on Ethereum; Technical Requirements; Understanding challenges in distributed systems; The CAP theorem; Horizontal scaling versus vertical scaling; Scaling Ethereum; Blockchain scalability trilemma; Ethereum scaling solutions; Block size; Altcoins; On-chain solutions; Off-chain solutions; ZK-SNARK; State channel with Raiden; Ethereum side chain with Plasma; Ethereum sharding and Casper; PoS consensus in Ethereum; Following up on EVM and lower-level protocol improvements; Implementing Ethereum 2.0 roadmap; Introducing cryptoassets and Ethereum token standards